RESPONSE OF MAIZE HYBRIDS TO IRRIGATION TREATMENTS AT SEMI-ARID ENVIRONMENT - Rekawt R. Ismaiel; S. I. Towfiq; T. H. Kareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This experiment was carried out during season of 2020 and 2021 at Erbil governorate to study the forage and grain yield performance of three maize hybrids Zea mays L. as influenced by irrigation skipping at different times. The experiment was laid out in split-plot design with three replications. The irrigation treatments were located at the main plots, and the hybrids were distributed at the subplots. Highly significant effects of irrigation treatments were recorded for forage, grain yield and most of its components at both seasons and their average. The differences among hybrids were not significant for forage yield at both seasons. It was significant for grain yield as the average of both seasons only. The fresh and dry forage yield was affected more by the skipping irrigation during the last two periods of skipping, and the same for the grain yield. That there are no significant differences between the control and skipping during the first period, as the significantly outperformed the grain yield in the last two periods of skipping.